2019
DOI: 10.4236/ojpsych.2019.93015
|View full text |Cite
|
Sign up to set email alerts
|

Community Perceptions of Indigenous Healers and Mental Disorders in Zimbabwe

Abstract: The World Health Organisation has made recommendations for partnerships between indigenous healing (IH) and biomedical therapy (BT) in the delivery of health services as a way of creating cultural sensitivity in mental health care (Bank, 2001). Yet, literature on prevalence, distribution, burden, and unmet needs for treatment of the mental disorders often exclude the role played by indigenous healing practitioners (IHPs). This study aimed to analyze mental health care from the perspective of communities on men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
(75 reference statements)
1
4
0
Order By: Relevance
“…The popular perceived causes of mental illness as perceived by traditional healers include a curse/witchcrafts, God/Allah punishment, poor social relationship, jealousy, hereditary, substance use and, food poisoning. In keeping with a previous study by Kajawu et al (2019) who indicated that witchcraft played a central role in the causation of mental health problems, the traditional healers of the Berta Community showed a strong belief about that. Similar perceptions and as to why people perform witchcraft on to others and how these curses cause mental illness have been described in previous studies from African countries like Nigeria and Ethiopia (Belachew et al, 2019; Ngobe, 2015; Teferra & Shibre, 2012).…”
Section: Discussionsupporting
confidence: 80%
“…The popular perceived causes of mental illness as perceived by traditional healers include a curse/witchcrafts, God/Allah punishment, poor social relationship, jealousy, hereditary, substance use and, food poisoning. In keeping with a previous study by Kajawu et al (2019) who indicated that witchcraft played a central role in the causation of mental health problems, the traditional healers of the Berta Community showed a strong belief about that. Similar perceptions and as to why people perform witchcraft on to others and how these curses cause mental illness have been described in previous studies from African countries like Nigeria and Ethiopia (Belachew et al, 2019; Ngobe, 2015; Teferra & Shibre, 2012).…”
Section: Discussionsupporting
confidence: 80%
“…The country's economy has collapsed, and this has had a massive impact on many people's mental health. It's been reported that out of the population of 1.4 million people which is 10 percent of the population are suffering from one or more of mental disorders (Kajawu et al, 2019).…”
Section: Challenges Of Mental Health In Zimbabwementioning
confidence: 99%
“…Resource Network for the Disabled mainly includes vocational rehabilitation donation projects, client assistance projects, rehabilitation training and supportive employment (Rothman, 2013); German Vocational Rehabilitation System emphasizes vocational training and compulsory employment measures (Wang, 2002); Hong Kong has learned and developed the vocational rehabilitation experiences of western countries, and its vocational rehabilitation services provided for patients with mental disorders include sheltered employment, assisted employment, comprehensive vocational rehabilitation service center, such as "Sun-Advances in Applied Sociology shine on the Road" training program and extended vocational rehabilitation program (Huang, 2010). A recent study completed in Zimbabwe shows that community-based indigenous therapy under local traditions and beliefs is effective in the treatment of mental disorders in low-income countries, and it is an important supplement to conventional biomedical therapy (Kajal, Chiweshe, & Mapara, 2019).…”
Section: Review On Community Vocational Rehabilitation Of Patients Wi...mentioning
confidence: 99%